Impact of fear of coronavirus disease 2019 on attention-deficit/hyperactivity disorder traits associated with depressive symptoms, functional impairment, and low self-esteem in university students: a cross-sectional study with mediation analysis - Tomoko Suzuki; Toshiyuki Ohtani; Michiko Nakazato; Ariuntuul Garidkhuu; Basilua Andre Muzembo; Shunya Ikeda (Environmental Health and Preventive Medicine)
Background: High levels of attention-deficit/hyperactivity disorder (ADHD) traits are associated with various outcomes, including depressive symptoms, functional impairment, and low self-esteem. Additionally, individuals with high levels of ADHD traits are reported to be more adversely affected by fear of coronavirus disease 2019 (COVID-19). The current study aimed to examine whether the association between ADHD traits and outcomes was partially mediated by fear of COVID-19 using mediation analysis. Methods: A cross-sectional study was conducted in a sample of university students in medical-related faculties (n = 1,166). ADHD traits, fear of COVID-19, depressive symptoms, functional impairment, and self-esteem were assessed using the adult ADHD Self-Report Scale, Fear of COVID-19 Scale, K6 Scale, Sheehan Disability Scale, and Rosenberg Self-Esteem Scale, respectively. We used linear regression analysis and the Paramed command in Stata to analyze whether fear of COVID-19 mediated the association between ADHD traits and outcomes. Results: ADHD traits were significantly associated with outcomes. Regarding the impact of fear of COVID-19, the results revealed a significant association between ADHD traits and fear of COVID-19, and between fear of COVID-19 and outcomes. The results of the mediation analyses showed that the association between ADHD traits and outcomes was partially mediated by the fear of COVID-19 (depressive symptoms: direct effect B = 1.029, 95% confidence interval [CI] 0.878, 1.181, indirect effect B = 0.021, 95% CI 0.002, 0.040; functional impairment: direct effect B = 0.786, 95% CI 0.593, 0.979, indirect effect B = 0.033, 95% CI 0.005, 0.060; self-esteem: direct effect B = −1.052, 95% CI −1.226, −0.878, indirect effect B = −0.024, 95% CI −0.046, −0.002). Conclusions: Developing preventive measures against the adverse impacts of pandemics like COVID-19 will be particularly important for individuals with high levels of ADHD traits in future.